Keber’ada’an Lgbt (Lesbian, Gay, Biseksual, dan Transgender) Dalam Perspektif Filsafat Proses Whitehead - Agus Hamzah; Siti Murtiningsih (Farabi, 2021)
The rise of LGBT cases is becoming a hot subject in the world as well as Indonesia, attracting researchers to see how it exists as an object as well as a subject. In addition, by knowing the existence of LGBT, it will also be known that its existence is a subjective, objective or relative phenomenon. This research is a type of library study research using the relevant theory reference, namely Whitehead's theory of Process Philosophy. From Whitehead's perspective, experiencing yourself intensively preoccupied with the conflict between oneself and all others in a harmonious union. Because values are determined by different things, the more an actual entity in the process of self-embodiment can distinguish itself from the other, the more intensive the actual entity experiences the subject, the more intensive it is to experience itself From the results of the literature study above showing that LGBT is the abnormality of sexual orientation influenced by the various factors that make it an independent subject. As a subject, LGBT is also an object for other subjects to form new subjects